The 1965 International Convention on the Elimination of All Forms of Racial Discrimination (ICERD) - Bethlendi, András (The Universal Protection of Human Rights, 2026)
Abstract: This chapter aims to provide a comprehensive analysis of the International Convention on the Elimination of All Forms of Racial Discrimination (ICERD), with a specific focus on Central and Eastern Europe (CEE). The paper describes the historical, political and legal background and circumstances that led to the creation of the Convention, analyses the content and specificities of the Convention in comparison with other international instruments, and discusses in detail the work of the treaty body Committee on the Elimination of Racial Discrimination (CERD). It discusses the mechanisms operated by the CERD: State reports, Inter-state complaints, Individual communications, Early warning and urgent action procedures, with particular reference to the CEE states. The study provides an exhaustive overview of the individual communications received from the region and addresses the issues of racial discrimination faced by Roma communities living in or originating from this area. Concluding remarks reflect on the ongoing challenges of racial discrimination in the region and the critical role of non-governmental organisations in advocating for marginalised groups. Finally, it raises pertinent questions about the implications of emerging technologies and artificial intelligence on racial equality, calling for adaptive legal frameworks to address new forms of discrimination in contemporary society. Keywords: ICERD, CERD, racial discrimination, discrimination, Roma